Prevention of urea toxicity in DNA and RNA content of a fresh water field crab, Barytelphusa guerini by using Sulphur containing amino acid Methionine as an additive - Kulkarni Arvind; Ratnakar Pravina; Balkhande Jayvardhan (International Journal of Life Sciences, 2016)
The objective of the present study was to investigate the prevention of toxicity of urea in DNA and RNA content of a fresh water field crab, Barytelphusa guerini by using sulphur containing amino acid Methionine as an additive. If fertilizer (urea) are used in high concentration than the concentration of urea above the tolerance limit is toxic to the aquatic animal including crab. In present study quantity of RNA was less than the DNA in both Male and Female. Sulphur containing amino acid Methionine an additive is useful to prevention of urea toxicity to a fresh water crab Barytelphusa guerini. This is the baseline work, more molecular work is needed for prevention of this type of toxicity in aquatic life.